High-energy gamma-ray and hard X-ray observations of CYG X-3. - Hermsen, W.; Bennett, K.; Bloemen, J. B. G. M.; Buccheri, R.; Jansen, F. A.; Mastichiadis, A.; Mayer-Hasselwander, H. A.; Özel, M. E.; Pollock, A. M. T.; Strong, A. W. (Astronomy and Astrophysics, 1987)
High-energy (70 MeV < E < 5 GeV) gamma-ray observations of Cyg X-3 by the ESA satellite COS-B and hard X-ray (14 keV < E < 140 keV) observations by the Leiden-MIT balloon experiment, Leimit, are presented. A comparison with, and a study of earlier results over the 14 decades in energy from 1 keV up to ≡1017eV indicates that the strong variability of Cyg X-3 over more than one order of magnitude at energies below 20 keV does not exhibit itself in the data collected at hard X-ray energies, and the power emitted per decade of energy reaches a minimum in the MeV-GeV region. If the primary gamma-rays up to 1015eV originate close to the central source, absorption by the keV X-rays in the Cyg X-3 binary system could explain the latter phenomenon.
Keywords: Absorption Spectra; Astrophysics; Cos-B Satellite; Gamma Ray Astronomy; Spectrum Analysis; Stellar Spectra; X Ray Astronomy; X Ray Binaries; X Ray Spectra